Effects of a Knowledge and Self-care Behavior Promotion Program on Knowledge, Behavior, and Hemoglobin A1C in Blood among Patients with Diabetes Mellitus - Kor-issaranuphab, Nittaya; Samrannet, Wanwisa; Intapan, Ranu (Princess of Naradhiwas University Journal, 2025)
This research was a quasi-experimental study with a one-group pretest-posttest design. The objectives of this study were to compare the knowledge, self-care behavior, and hemoglobin A1C levels in blood before and after participating in the knowledge and self-care behavior promotion program. The sample consisted of patients with diabetes mellitus type 2 receiving services at the Samakkhi Community Chronic Disease Clinic, Mueang District, Maha Sarakham Province. A simple random sampling method was used to select 33 participants. The intervention tool was the knowledge and self-care behavior promotion program, which lasted for 16 weeks. Data collection instruments included a personal information questionnaire, a self-care knowledge questionnaire of patients with diabetes mellitus with a Kuder-Richardson 20 reliability coefficient of 0.76, and a self-care behavior questionnaire of patients with diabetes mellitus with a Cronbach’s alpha reliability coefficient of 0.82. Data were analyzed using descriptive statistics and paired t-tests. Results found that after participating in the program, the average self-care knowledge scores of the participants were significantly statistically higher than before participating in the program (t = 15.87, p < .05). The average self-care behavior scores were also significantly statistically higher than before participating in the program (t = 10.00, p < .05), and the average hemoglobin A1C levels in blood decreased significantly statistically after participating in the program (t = -6.89, p < .05). Therefore, relevant agencies and healthcare personnel can apply the program in caring for patients with diabetes mellitus, self-care behavior modification, and blood sugar level control to prevent further complications in patients with diabetes mellitus.